Doing business in Russia : a concise guide. - Zhuplev, Anatoly, 1948-, (International business collection., 2017)
Russia is the world's largest geographic area, major economy, and important power in the global political-economic landscape. Over the past quarter century, following the landmark dissolution of the U.S.S.R., Russia has become a premier global marketplace despite remaining enigmatic and challenging. The book strives to serve as a concise guide in understanding Russia from an international business perspective. You will learn about strategic issues, business drivers, pros, cons, costs, and risks of international expansion. The coverage includes analytical tools, practical applications, sources of information, and assistance in international business research. These are followed by Russia's macroeconomic profile, drivers, strategic strengths and weaknesses in the comparative global context, including its international market attractiveness and primary opportunities for U.S. companies. The book examines Russia's main industries, their profiles, dynamics and business attractiveness, consumer trends, and marketing strategies. The discussion of Russia's regions covers regional subdivisions and economic profiles with the focus on the city of Moscow commanding top attractiveness from the domestic and international business perspective. The book covers the drivers and trends of the Russian small business sector and entrepreneurial business venturing. Despite the onslaught of capitalism and globalization, Russia retains its relationship-driven culture. The book provides insights in Russian culture by evaluating the determinants of Russian culture, its national profile in major global cross-cultural studies, and practical cultural applications in business, negotiations, and communications. The book's pedagogy includes critical information sources and skill development exercises and cases on doing business in Russia.